TFA and EPA Productivities of Nannochloropsis salina Influenced by Temperature and Nitrate Stimuli in Turbidostatic Controlled Experiments - Klaus Heinrich Vanselow; Kai Marxen; Rüdiger Schulz; Maren Hoffmann (Marine Drugs, 2010)
The influence of different nitrate concentrations in combination with three cultivation temperatures on the total fatty acids (TFA) and eicosapentaenoic acid (EPA) content of Nannochloropsis salina was investigated. This was done by virtue of turbidostatic controlled cultures. This control mode enables the cultivation of microalgae under defined conditions and, therefore, the influence of single parameters on the fatty acid synthesis of Nannochloropsis salina can be investigated. Generally, growth rates decreased under low nitrate concentrations. This effect was reinforced when cells were exposed to lower temperatures (from 26 °C down to 17 °C). Considering the cellular TFA concentration, nitrate provoked an increase of TFA under nitrate limitation up to 70% of the biological dry mass (BDM). In contrast to this finding, the EPA content decreased under low nitrate concentrations. Nevertheless, both TFA and EPA contents increased under a low culture temperature (17 °C) compared to moderate temperatures of 21 °C and 26 °C. In terms of biotechnological production, the growth rate has to be taken into account. Therefore, for both TFA and EPA production, a temperature of 17 °C and a nitrate concentration of 1800 µmol L-1 afforded the highest productivities. Temperatures of 21 °C and 26 °C in combination with 1800 µmol L-1 nitrate showed slightly lower TFA and EPA productivities.